(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this article, the main task of pedagogical theory and practice is the formation of a professional worldview of students on the basis of chemical knowledge, its relevance, the methodological foundations of the formation of a professional worldview, the theoretical foundations of the formation of a professional worldview of students on the basis of chemical knowledge.